Para que tenham vida: A Regra bulada de São Francisco - Carbajo Núñez, Martín (Revista Eclesiástica Brasileira, 2023)
Este artigo responde à celebração do oitavo centenário da Regra bulada de São Francisco (29.11.1223), que é uma das quatro grandes Regras da Vida Consagrada, e analisa sua força inspiradora no atual contexto secularizado da sociedade. Não é só um texto jurídico, mas também um documento espiritual, uma guia “para viver segundo a forma do santo Evangelho” (1ª parte). Quem detém autoridade tem que estar a serviço do processo vital que a Regra propõe, atuando como mães que cuidam da vida (2ª parte). A terceira parte apresenta sua atualidade e a importância de uma liderança inspiradora, que promova processos de transformação, para enfrentar os desafios da Vida Consagrada. Abstract: This article is intended as a contribution to the celebration of the eighth centenary of the Later Rule of St. Francis (Nov. 29, 1223), which is one of the four great Rules of consecrated life, and analyzes its inspirational force in the current secularized context of society. It is not only a juridical text, but also a spiritual document, a guide “to live according to the pattern of the Holy Gospel” (part 1). Those in authority must be at the service of the vital process, acting as mothers who take care of life (part 2). The third part presents the Rule’s current relevance and the need of an inspiring leadership that promotes processes of transformation to address the present challenges of religious life. Keywords: Francis of Assisi; Franciscans; Later Rule; Religious Life; Leadership.